PUBLIC SPEAKING BAGI KADER POSYANDU DI PUSKESMAS PEMBANTU TALANGSUKO, TUREN, KABUPATEN MALANG - Karim, Bima Aminul; Nur Aini, Indah; Martina, Inu (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2023)
The direct presence of health workers to deliver health materials is considered more effective because people will focus on and understand it better. Unfortunately, the number of health workers in the community is limited therefore committed cadres will help them. These cadres already have the ability to convey information in front of many people, yet they still need to practice polishing and renewing their public speaking techniques and ability. Therefore, this community service aims to give a workshop on public speaking for health promotion cadres. Before the workshop, the community service team observed the health promotion cadres and then decided on the theme. Fifteen cadres from Talangsuko, Turen, Malang District were involved in the workshop. As a result of the evaluation (post-test and role play, the knowledge and public speaking of cadres increased. To make their health promotion more perfect, they just have to practice choosing new words and using stressed vowels on important words.